Exact solutions to a massive charged scalar field equation in the magnetically charged stringy black hole geometry and Hawking radiation - Sakallı, İzzet; Al-Badawi, Ahmad (Canadian Journal of Physics, NRC Research Press, 2009)
Exact solutions of a massive complex scalar field equation in the geometry of a Garfinkle-Horowitz-Strominger (stringy) black hole with magnetic charge is explored. The separated radial and angular parts of the wave equation are solved exactly in the non-extreme case. The angular part is shown to be an ordinary spin-weighted spheroidal harmonics with a spin-weight depending on the magnetic charge. The radial part is achieved to reduce a confluent Heun equation with a multiplier. Finally, based on the solutions, it is shown that Hawking temperature of the magnetically charged stringy black hole has the same value as that of the Schwarzschild black hole.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1139/P09-024) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; black holes; hawking radiation